2013
DOI: 10.2495/secm130141
|View full text |Cite
|
Sign up to set email alerts
|

The use of nitriding to enhance wear resistance of cast irons

Abstract: This research is focused on using nitriding to enhance the wear resistance of austempered ductile iron (ADI), ductile iron (DI), and gray iron (GI). Three gas nitriding processes, namely "Gas nitriding + nitrogen cooled down to 800 o F" (Blue), "Gas nitriding + cooled down to 300 o F" (Gray), and "Gas nitriding + oil quenched" (Oil) were used. This study was carried out through optical metallography, roughness measurements, microhardness, and SEM. The ball-ondisc wear tests were conducted under lubricated cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Sokolov et al [9] reported that when gray cast iron was exposed to the ion nitriding process, the corrosion resistance of specimens would be increased in 0.7 M NaCl solution. Yang [10] used the nitriding process to improve the wear resistance of cast irons. It was found that the friction coefficient of cast irons in the presence of the compound layer would be reduced to a value of 0.04.…”
Section: Introductionmentioning
confidence: 99%
“…Sokolov et al [9] reported that when gray cast iron was exposed to the ion nitriding process, the corrosion resistance of specimens would be increased in 0.7 M NaCl solution. Yang [10] used the nitriding process to improve the wear resistance of cast irons. It was found that the friction coefficient of cast irons in the presence of the compound layer would be reduced to a value of 0.04.…”
Section: Introductionmentioning
confidence: 99%
“…Wear is affected by a variety of conditions, such us the type of lubrication, loading, speed, temperature, materials, surface finish and hardness. For example, nitrided steels are widely used due to their superior hardness and attractive surface hardness, fatigue life and tribological properties [1]. The prediction of wear is therefore an important part in mechanical engineering.…”
Section: Introductionmentioning
confidence: 99%